Dynamic Capabilities in Digital Transformation: Unpacking the Mediated Effects of IS Integration on Managerial Agility and Decision Speed - Ikbal, Muhammad (Indonesian Scientific Publication, 2025)
This study examines how information system (IS) integration affects managerial decision speed in Indonesian public and private sector organizations. Using survey data from 185 organizations and structural equation modeling, we test a mediation model involving system quality, organizational agility, and big data analytics capability (BDAC). Results show that IS integration directly accelerates decision speed and indirectly strengthens it through the three mediators. Private sector firms benefit more due to higher digital readiness and flexible structures, while environmental turbulence further shapes outcomes. The study contributes by extending IS success theory with dynamic capabilities and highlighting sector-specific strategies for digital transformation. Findings emphasize that successful digital transformation requires not only technical solutions but also cultural, structural, and strategic alignment.